Genetic research of neuropsychiatric disorders in Latin America - Contreras Rojas, Javier (2019)
Abstract: Background: Investment in research in middle and low-income countries (LMIC) is generally under 1% of the GNP. According to Saxena et al, only 10% of mental health research is directed to the needs of the 90% of population living in the 153 low and middle-income countries (LMIC) (Saxena et al., 2006). Despite the advances in the identification of genetic variants for neuropsychiatric disorders in European and Asian populations, research of these disorders in Latin American populations remains limited. Methods: We reviewed scientific reports on genetic research of neuropsychiatric disorders from Latin America during the last 10 years (2007-2017). We found 78 published papers in local and international peer-reviewed journals. Results: We divided the publications by geographical regions: South America 41 (52%), Central America 23 (30%), Caribe 6 (8%) and Mexico alone 8 (10%). For the total 41 papers from South America, the countries with the highest number of publications are Brazil: 13 (32%) and Colombia: 12 (30%). For the Mesoamerican Region (Mexico and Central America), we found that only Mexico and Costa Rica have a significant contribution, either alone or in collaboration. Out of the 78 publications, the overall funding source origin is local: 44 (56%). The international agencies that provided support for these researches are: NARSAD, NIH, OCD Foundation and Wellcome Trust. Twenty-four (31%) were family-based versus 54 (69%) case-control studies. Costa Rica has played a leading role in genetic research of neuropsychiatric disorders in our region. The study's results have been published in 102 scientific research papers during the last 25 years. Our research group at the University of Costa Rica (biggest public university with 30,000 students and over 60% of scientific papers from CR) has over 25 years of studying the genetics of neuropsychiatric disorders in Costa Rica, including deafness (first gene for non-syndromic deafness mapped in CR), schizophrenia, bipolar disorder, successful cognitive aging, among others. During the last 13 years, we conducted 12 scientific research projects (2 research training programs funded by Fogarty, 9 research projects to study the genetics of neuropsychiatric disorders and 1 project to form a network that will study resilience and protective factors for neuropsychiatric disorders in LMICs). Because of big pedigrees, good medical and genealogical records, excellent participation of families that also live relatively close together, we have done mostly family studies but also have population-based studies on trios (parents and affected child). Most research is funded by foreign sources such as NIH, ICGEB, other NGOs and limited local sources (Expenditure on research as % of GDP: 0.54%). Conclusions: This shows significant differences in scientific reports among sub regions and a low local investment in genetic research of neuropsychiatric disorders in Latin America.